PEMETAAN ANCAMAN BENCANA TANAH LONGSOR BERBASIS SISTEM INFORMASI GEOGRAFIS (Studi Kasus : Kecamatan Bener, Kecamatan Loano dan Kecamatan Kaligesing, Kabupaten Purworejo) - Aulia, Fatah; Sasmito, Bandi; Qoyimah, Shofiyatul (Elipsoida : Jurnal Geodesi dan Geomatika, 2024)
Purworejo Regency is one of the districts in Central Java that often experiences natural disasters. Based on the Indonesian Disaster Risk Index, Purworejo Regency is in the high category or prone to natural disasters. Based on BPBD data from Purworejo Regency throughout 2021, Purworejo Regency often experiences landslides with high landslide intensity in Bener, Loano and Kaligesing Districts. This condition is the basis for this research as one of the disaster mitigation efforts in the sub-district area. This research is based on a Geographic Information System using Minister of Public Works Regulation No.22/PRT/M/2007 and AHP. Both methods were verified with landslide disaster event data. The results of landslide threat mapping based on Minister of Public Works Regulation No.22/PRT/M/2007 showed that the high zone threat was 6.67% or an area of 1,561,205 Ha, the medium zone was 77.52% or an area of 18,140,315 Ha, and 15.80% or an area of 3,698.145 Ha is in the low category. Meanwhile, the AHP results showed that the high threat area for landslides was 12.45% or an area of 2,913,889 Ha, the medium zone was 77.14%, or an area of 18,050,276 Ha, and 10.41% or an area of 2,435,500 Ha was in the low category.Keywords: Landslides, Permen PU No.22/PRT/M/2007, AHP